Pendidikan Akhlak Aplikatif Integratif di Sekolah: Applicative Integrative Moral Education in Schools - Ahmad Royani (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2015)
The emergence of counter-productive elements in the world of education has led to symptoms among youths, even adults, showing that they ignore the moral values and manners needed in a civilized society. Concerns about moral decadence are like a double-edged knife. If you look for the root of the problem in others, it essentially lies within yourself; thus, blaming others means blaming yourself. Therefore, it is necessary to find solutions and moral education through appropriate actions. This research on the